تدريس (العاميات) للناطقين بغير اللغة العربية بين الرفض والقبول - ساتي, خولة حسن عثمان (Gezira Journal of Educational Sciences and Humanities; Vol 20 No 1 (2023), 2026)
هدف هذا البحث إلى بيان رؤيٍة واضحة في ماهيّة اللغة التي يجب تعليمها لمتعلمي اللغة العربية للناطقين بغيرها؛ حيث لاحظت الباحثة أن العاميّة صارت واقعاً يفرض نفسه في هذا المجال. ويميل بعض معلمي اللغة العربية إلى تعليمها نزولاً على رغبة بعض المتعلِّمين فيها. منهج هذا البحث هو المنهج الوصفي التحليلي، وقد تم تصميم استبانة تم توزيعها على عددٍ من المعلمين في بلدانٍ مختلفة من أجل معرفة آرائهم،  اعتماداً على الدراسات السابقة في هذا المجال و إجابة  بعض المختّصين على أسئلة الاستبانة.  خلصت الدراسة إلى نتيجةٍ - واضحة - مؤدّاها أنّه لابد من الإقرار بوجود العاميّات والتسليم بها كواقعٍ لغوي وحاجة بعض الدارسين إليها؛ ولكن ذلك لا يعني اعتمادها في منهج تعليم اللغة العربية  للناطقين بغيرها. قدّمت الدراسة بعض المقترحات والتوصيات التي تمّثلت في ضرورة أن تتبنّى مؤسّسات تعليم اللغة العربية للناطقين بغيرها في البلاد العربية؛ تأليف كتبٍ موحّدة باللغة الفصيحة وإنشاء مواقع الكترونية لتعليمها باللغة المعاصَرة؛ للحدِّ من انتشار الكتب المؤلّفة بالعاميات والمواقع الإلكترونية التي تدرِّس العاميات، والاهتمام بتأهيل معلمي اللغة العربية للناطقين بغيرها ؛ لأن عبء التخلٌّص من العاميات يقع على عاتقهم. وعليهم تجنٌّب استعمال العاميات في التدريس وحث الدارسين على عدم استعمالها.          The paper aimed at giving a lucid vision on the type of Arabic variety to be taught to non-native learners. The researcher has noticed that colloquial Arabic has become undeniable, self-imposing reality in this field. In addition, some language teachers tend to teach colloquial Arabic in response to the preferences of some students. The study followed the descriptive, analytical method. A questionnaire was designed and distributed to a number of teachers working in different countries to fill in. Based on previous studies conducted in this field as well as on some specialists' responses to the questionnaire, the study has reached the following findings: It is essential to acknowledge the existence of colloquial varieties and recognize them as a linguistic reality that meets the needs of some learners. However, this does not mean their inclusion in Arabic language syllabi for non-native speakers. The study has put forward the following suggestions and recommendations: It is essential that Arabic language teaching institutions for non-native speakers in the Arab world adopt the development of unified textbooks in modern standard Arabic and establish electronic platforms for teaching it using a contemporary style. Furthermore, it is necessary to curb the proliferation of books written in colloquial dialects and websites that promote their instruction. Furthermore, emphasis must be placed on qualifying Arabic language teachers for non-native speakers, as the burden of eliminating colloquialisms rests on their shoulders. They must avoid using colloquial varieties in instruction and encourage learners to refrain from using them as well.